Evaluation of the LI-710 evapotranspiration sensor in comparison to full eddy covariance for monitoring energy fluxes in perennial and annual crops - Srinivasa Rao Peddinti; Isaya Kisekka (Agricultural Water Management)
Reliable and low-cost sensors for measuring evapotranspiration (ET) and associated energy fluxes are crucial for hydrologic monitoring and water management; however, conventional methods such as eddy covariance (EC) can be prohibitively expensive and complex. This study evaluates the performance of the LI-710 sensor across perennial (citrus, almond, pistachio) and annual crops (processing tomatoes) by comparing daily ET, sensible heat flux (H), and latent heat flux (LE) measurements with those from full EC systems under California’s Central Valley climatic conditions. Measurements from the LI-710 were corrected for unclosed energy balance using an energy-balance-residual (EBR) method that incorporates independent net radiation and soil heat flux data. Uncorrected LI-710 fluxes exhibited a consistent underestimation, as reflected in low or negative Nash–Sutcliffe efficiency (NSE) values. For ET, processing tomato NSE increased from 0.35 to 0.94 with EBR correction, citrus from 0.32 to 0.73, almond from −2.09 to 0.79, and pistachio from 0.72 to 0.95. H improved similarly (processing tomato: 0.86–0.97; citrus: 0.13–0.67; almond: −0.35 to 0.75; pistachio: 0.20–0.85), while LE accuracy rose from 0.44 to 0.95 in processing tomatoes, −0.10 to 0.77 in citrus, −1.51 to 0.76 in almonds, and 0.71–0.93 in pistachios. Corresponding reductions in root mean square error (RMSE) confirmed that EBR-corrected LI-710 measurements closely aligned with EC observations, effectively capturing seasonal peaks and phenological transitions. These results highlight the LI-710 sensor’s potential as a lower-cost, user-friendly alternative to full EC systems for routine flux monitoring, provided that energy-balance adjustments are implemented. Such an approach can support precision irrigation and sustainable water management, particularly in regions facing increasing pressures on freshwater resources.